Valorisation of frozen chestnut by-products: technological challenges for the production of gluten-free flour - Borges, Ana (2019)
The industrial process of freezing chestnuts generates 5560% of by-products. This study aimed to valorise these low-value by-products by producing high-value chestnut flour. Two flour production processes were evaluated, using raw (RCF) and cooked (CCF10, CCF30, CCF50) chestnut by-products during 10, 30 and 50 min. The highest production yield was obtained for RCF (43.6±1.0%) followed by CCF10 (38.0±1.0%). Regarding flour composition, CCF50 presented the smaller protein, fat, fibre and ash contents (P<0.05). For colour, aw, pH and sedimentation index, no significant differences were observed namely between RCF and CCF10 (P>0.05). The CCF10 flour also presented the smallest particle size. The highest peroxide index was found in CCF50 penalizing its acceptance by consumers due to the evidence of rancidity, emphasizing that long time-periods of cooking must be avoided. Finally, up to 129 days of storage, under no temperature or lighting controlled conditions, all chestnut flours showed to be stable overtime.